The Concept of Connection as an Enhancer of the Professional Training of the Engineer: Experiences at Universidad Autónoma De Nuevo León - Castillo-Elizondo, Jaime Arturo (2019)
The connection between the university and the environment is a constantly updated topic. In the case of the engineering is necessary for the achievement of adequate training. The main objective of this study is to assess the possibilities of linking engineering schools and faculties to train professionals who adapt and, at the same time, contribute to transform their environment ethically and responsibly. A non-experimental descriptive design was used to identify those gaps that need to be filled from a theoretical perspective as a basis for the practical actions described. The participants were students of last semesters of 11 engineering careers. The limited presence of the integral approach of that connection is critically analyzed in the consulted sources. From this point, a series of principles for the connection with the environment were determined. A conclusive result of the first phase of the research is presented. This result describes linking actions oriented to the professional development of the students, whose results will be measured in a next stage. These proposals constitute a reference from its conception, functions, and purposes: the conditions, forms, and methods must be adapted to the context. It is concluded that the link between the university and the environment lacks an integral approach and systematization, and constant innovation. It is also concluded that, in the faculties, there are multiple possibilities for the innovation of new avenues for the professional training of the engineer.